Verb adjectives and meanings in functional linguistics - Kamil Saadoon, Haider; Mohammed Jebur, Hayder (Al-Adab Journal, 2021)
Linguistic curricula in general represented a validation of the linguistic development in the areas of semantics, synthesis, and access to deliberation, The functional curriculum, which was based on observing the deliberative dimension of words, was the most prominent of the modern linguistic approaches, Historians of linguistic research distinguished between two main currents: a (sour) trend that stands in its study of natural languages as they are structured and hardly goes beyond them. And a current (functional) attempts to describe the structure of natural languages by linking them with the functions these languages perform within human societies, Formal theories view language as an abstract system or a group of abstract sentences that perform a group of functions, and this research sheds light on functional linguistics in general and action related to it in particular to reflect the effect of this approach on linguistic research.